Sisi Gelap Kepemimpinan Pentakostal-Karismatik - Pranoto, Minggus M. (Faculty of Theology Duta Wacana Christian University, 2020)
Abstract This article highlights a critical question: why is Pentecostal-Charismatic leadership vulnerable to various scandals? This model of leadership often exposes the dark side of leadership characterized by the issues of money, sex, and power. This study suggests that Pentecostal-Charismatic leaders are often trapped in the model of personalized charismatic leadership that is based on misinterpretation of the doctrine of being Spirit-filled. The method used in this article is that of practical theology relating the framework of socialized charismatic leadership to the theological concept of the church (ekklesia) as the body of Christ and the fellowship of the Holy Spirit. Abstrak Tulisan ini menyoroti pertanyaan kritis: mengapa kepemimpinan Pentakostal-Karismatik rentan terkena berbagai skandal? Model kepemimpinan ini acap kali memunculkan sisi gelap kepemimpinan yang ditandai oleh masalah-masalah keuangan, seksual, dan kekuasaan. Kajian ini mengungkapkan bahwa para pemimpin Pentakostal-Karismatik seringkali terjebak dalam model personalized charismatic leadership yang didasari oleh penafsiran yang keliru atas doktrin being Spirit-filled. Metode tulisan ini termasuk dalam ranah teologi praktis yang mengaitkan kerangka berpikir socialized charismatic leadership dengan konsep teologis tentang gereja (ekklesia) sebagai tubuh Kristus dan persekutuan Roh Kudus.